Exclusive breastfeeding and its effect on growth of Malawian infants: results from a cross-sectional study. (February 2015) - Kuchenbecker, J.; Jordan, I.; Reinbott, A.; Herrmann, J.; Jeremias, T.; Kennedy, G.; Muehlhoff, E.; Mtimuni, B.; Krawinkel, M. B.
<x content-type="archive" xml:space="preserve">Abstract</x> Background: For the optimal nutrition of children under 2 years of age, it is considered important that they be exclusively breastfed for the first 6 months before being given complementary food. Aims and Objectives: A cross-sectional nutritional baseline survey was undertaken in 2011 in the Kasungu and Mzimba Districts of Malawi to assess the nutritional status of children under 2 years of age and its determinants in order to prepare a nutrition education intervention programme. The intention of this study was to assess the nutritional status of infants aged 0–<6 months with regard to food intake. Methods: Interviews were conducted on randomly selected families with children under 2 years; anthropometric measurements were obtained from mothers and their children. Only infants between 0 and <6 months were selected for analysis (n = 196). An ANCOVA test was performed on age of the infant with mothers' height and weight as covariates. Results: Prevalence of stunting (infants' length-for-age Z-score (LAZ) <−2SD) was 39%, wasting (WLZ <−2SD) 2%, and underweight (WAZ <−2SD) 13%. Of the infants under 6 months, 43% were exclusively breastfed. Predominant breastfeeding and mixed breastfeeding were less common (21% and 36%, respectively). The ANCOVA confirmed the association between exclusive breastfeeding and LAZ and WAZ: exclusively breastfed infants had a higher mean (SE) LAZ (−1·13, 0·12) and WAZ (−0·41, 0·13) than infants not being exclusively breastfed (−1·59, 0·11, and −0·97, 0·11, respectively). There was no overall significant association between breastfeeding practice and WLZ. Conclusion: Exclusive breastfeeding of infants under 6 months is associated with higher mean LAZ and WAZ. Promotion of exclusive breastfeeding in low-income countries is important in preventing growth retardation.